Kodamaea Ohmeri: a rare fungus causing a severe case of necrotizing fasciitis - Jimenez, Mercy; Seltzer, Emily S.; Shakil, Javeria; Louis, Martine (International Surgery Journal, 2020)
Necrotizing soft tissue infection, NSTI, involves the soft tissue characterized by rapid spread of infection and consequent cell necrosis. NSTI, in particular necrotizing fasciitis (NF), is a significant disease burden in the US with an annual mortality of 4.8 per 1,000,000 person years. Here we describe a rare fungal pathogen, Kodamaea Ohmeri, as a cause of NF in a diabetic but otherwise healthy male patient. In the past K. Ohmeri has been described in children, immunocompromised individuals, and in cases with IV catheters and prolonged use of IV antibiotics. A febrile and hypotensive male (LRINEC score of 6) presented after sustaining abrasions of his right lower extremity. He was initially started on broad-spectrum antibiotics and underwent surgical exploration. During the following weeks, the patient developed sepsis and endured a total of four debridement. Wound cultures resulted K. Ohmeri with sensitivity to miconazole and voriconazole. Anti-fungal, silver dressings and wound vacuum, were utilized to assist in treatment and tissue granulation. To our knowledge, this is the first case describing Kodamea ohmeri as a causative agent of NF. K. Ohmeri should be on the radar of the health care providers taking care of patients with NF, especially in the context of intermittent bouts of sepsis and prolonged hospital course. Our case illustrates the fact that prompt identification, addition of fungal cultures and appropriate surgical treatment are crucial to improve patient outcomes.